A comparison between two didactical approaches on shielding problems in an electromagnetic compatibility course – Analytical method versus simulation method. Issue 2 (April 2016) - Aciu, Lia E; Cazan, Ana-Maria; Ogrutan, Petre L
The subject of electromagnetic compatibility is a compulsory one, taught to students from electrical engineering and applied electronics study programmes. We present a comparative study between the current teaching method of shielding calculation and a new simulation-based teaching approach. In the academic year 2013–2014, the effectiveness of the new method was evaluated by analyzing the answers provided by the students to the items in a questionnaire along with their final lab test scores.